D-mannitol@silica/graphene oxide nanoencapsulated phase change material with high phase change properties and thermal reliability. (15th June 2020) - He, Lijuan; Mo, Songping; Lin, Pengcheng; Jia, Lisi; Chen, Ying; Cheng, Zhengdong
Highlights: A method was developed for preparing D-mannitol@silica/graphene oxide nanocapsules. Graphene oxide incorporation had little effect on latent heat of the nanocapsules. The thermal stability of the nanocapsules was enhanced. The thermal reliability index was 96.1% after repeated thermal cycling. The thermal conductivity was increased to 129% through nanoencapsulation. Abstract: Sugar alcohols have considerable potential for usage in medium-temperature thermal energy storage applications; however, they suffer from poor thermal reliability and low thermal conductivity. Nanoencapsulation is an effective approach to improve the thermal energy storage performance of the phase-change materials. Until now, nanoencapsulation of sugar alcohols with a high phase-change performance has been rarely reported. The objective of this study is to develop a method for the nanoencapsulation of sugar alcohols with an enhanced phase-change performance. D-mannitol nanocapsules with a silica–graphene oxide composite shell were synthesized and investigated to demonstrate the validity of this novel method. The morphology, size distribution, and core–shell microstructure of the nanocapsules were observed using a scanning electron microscope, particle size and zeta potential analyzer, and transmission electron microscope. In addition, the phase-change performance of the nanocapsules was studied using a differential scanning calorimeter, a thermogravimetric analyzer, and weight loss and appearance investigation. The results demonstrate that the melting and solidifying latent heat of the nanocapsules are 216.7 and 174.4 kJ/kg, respectively. The energy storage efficiency of the nanocapsules was 75.8% and its 96.1% was maintained after repeated thermal cycling. Compared with pure D-mannitol, the thermal conductivity of the nanocapsules was observed to increase by up to 128.6%. The novel nanocapsules exhibited good medium-temperature thermal energy storage prospects.